Comparison Of Corporate Bankruptcy Predictions Based On The Altman Model And Springate Approach: Case Study of the Technology Sector Listed on the IDX for the 2021-2023 Period - Hidayat, Ahsan Nurfalah; Mutmainah, Isbandriyati; Marnilin, Feni (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study was conducted to determine the financial performance of technology sector companies from the analysis of bankruptcy prediction using the Altman Z-Score and Springate S-Score methods and compare the accuracy and type error of the two methods in the 2021-2023 period. This study uses secondary data obtained from the Indonesia Stock Exchange using quantitative descriptive analysis techniques. The determination of the sample in this study uses a nonprobability sampling method, precisely with a purposive sampling technique. The results of this study show that based on the Altman Z-Score method, there are 4 technology sector companies that have the potential to experience bankruptcy for 3 consecutive years, including ATIC, DIGI, CASH, ENVY. Based on the Springate S-Score method, it is indicated that 4 companies have the potential to go bankrupt for 3 consecutive years, including DIGI, CASH, ENVY, CYBR. The accuracy and type error rate obtained for three years in technology sector companies based on the Springate S-Score method resulted in a higher accuracy of 72% in 2022 with lower type errors compared to the Altman Z-Score method. Keywords: Technology Sector, Bankruptcy, Altman Z-Score, Springate S-Score